Evolution Wave Condition Using WAVEWATCH III for Island Sheltered Area in the South China Sea - Li Zou; Liangyu Liu; Zhen Wang; Yini Chen (Journal of Marine Science and Engineering, 2023)
Wave conditions around islands in the South China Sea (SCS) are of significant interest due to their importance for marine operations and coastal engineering. Understanding and accurately predicting wave characteristics in this region are crucial. In this study, the third-generation wave model WAVEWATCH III is employed to examine wave conditions around islands in the SCS. According to the water depth and significant wave height, the sea state around the island was classified into two categories: typhoon sea state and moderate sea state. Several popular wind input–dissipation source terms (ST2, ST4 and ST6) are used to assess the typhoon sea state and the moderate sea state separately. The results are validated by field wave data. ST4 and ST6 show good performance in significant wave height for moderate sea states, while ST2 is good at the mean wave period. For the typhoon sea state, ST2 gives the best results in significant wave height with larger correlation coefficients and a smaller RMSE. The above results provide valuable insights into the effects of different source terms on the accuracy of wave simulations for different sea states. The spatial distribution of the significant wave heights is also demonstrated with ST2, which may be useful for assessing the wave conditions of marine structures from the large scale of the SCS to the island scale of the Yongle Atoll.